A função de operação estabelecedora condicionada transitiva de estímulos verbais e não verbais: uma análise experimental - Veiga, Dhayana Inthamoussu (2010)
The purpose of the present study was to verify if verbal stimuli could exert the function of transitive conditioned establishing operation (TCEO) and if the establishment of the TCEO function would differ between verbal stimuli probably produced by different histories of reinforcement (tacting / manding / autoclitic relations) and would differ between verbal and non verbal stimuli. The participants were 15 female and 4 male (between 18 and 24 years old). A software managed the presentation of the task and the manipulation of the operative contingencies. The task was presented as a game, similar to a slot machine, in which a mouse and a joystick were used to produce points which could be exchanged by an amount of money. The experimental design was based in Ravagnani (2004) and consisted of: a preliminary phase (discrimination and chaining) and Phases 1, 2 and 3. The purpose of Phase 1 was to establish a TCEO, with one word ( press , fruits or don t press ), a pseudo-word ( tabilu ) or an abstract image (╣╣╣╣╣╣╣╣╣). The TCEO was established through the following contingency: in the presence of one of the five stimuli the first instance of the response should be emitted and once the VR12 was completed the color of a circle was changed from grey to green during 3 seconds. In the presence of the Green circle the response of pulling the joystick s handle produced one point. If the first response instance was emitted in the absence of the presumed TCEO the completion of the VR12 would produce the color change of the circle, however, the response of pulling the joystick s handle would not produce points. Phase 2 had the aim to observe the possible effects of the non changing color of the circle as a consequence for the of completion of the VR12 on the behavioral chain. In this phase, all VR12 started either in the presence or in the absence of the presumed TCEO did not produce the 3 sec color change in the circle, which was grey. However, pulling the joystick s handle during the first three sec immediately subsequent to the VR12 completion (started in the presence of the presumed TCEO) produced points. On Phase 3, contingencies identical to those of Phase 1 were operative with the purpose to verify if the changes in the behavior of the participants possibly observed during Phase 2 would remain. Phase 1 results indicate that, for 16 of 19 participants the TCEO was established, despite the stimuli utilized. For 13 of these 16 participants, results clearly showed that the conditioned reinforcer omission produced behavioral changes which indicate extinction process. It suggests that the green circle exerted conditioned reinforce function, established by the TCEO. Phase 3 results show that the behavioral chain was sistematically completed by all 16 participants. Some evidence of differences between the effects produced by the different stimuli established as TCEO during Phase 1 were observed. However this study could not verify the establishment of systematic relations